Gestational weight gain and newborn anthropometric outcomes in rural Bangladesh - Kac, Gilberto; Arnold, Charles D.; Matias, Susana L.; Mridha, Malay K.; Dewey, Kathryn G. (Wiley Online Library, 2022)
This article was published in Maternal Child Nutrition [ © 2019 John Wiley & Sons Ltd.] and the definite version is available at: https://doi.org/10.1111/mcn.12816. The Journal's website is at: https://onlinelibrary.wiley.com/doi/ftr/10.1111/mcn.12816